Person‐centred care in speech‐language therapy research and practice for adults: A scoping review. Issue 2 (8th January 2022) - Forsgren, Emma; Åke, Sabina; Saldert, Charlotta
Abstract: Background: Person‐centred care (PCC) has shown positive effects in various health‐care settings and therefore is desirable in clinical work. However, as PCC is still being developed, the literature reflects a heterogeneous use of both terminology and conceptualisation. This lack of consistency hinders the implementation or adaptation of PCC in general and in select fields of practice such as speech‐language therapy (SLT). Aims: To describe how the concept of PCC manifests in current speech and language therapy research and practice for adult patients. Methods & Procedures: Searches for published literature were conducted in five databases (PubMed, Scopus, CINAHL, Psych INFO, and Linguistics and Language Behaviour Abstracts) using search terms related to PCC and SLT. Records were included if they involved an adult population, were written in English, and focused on PCC and SLT irrespective of year of publication. Main Contribution: A total of 134 records published 1996–2020 were included in this review. Many of these records were discussion papers that described how speech‐language therapists (SLTs) can or should work in a person‐centred way. The search did not find any records that explore the implementation, effects, or patients' views of person‐centred SLT. This literature review revealed that person‐centred SLT practice mainly relates to the International Classification of Functioning, Disability, and Health framework, and the Life Participation Approach to Aphasia. Studies incorporating exploration of proposed clinical routines of PCC demonstrate specific context‐dependant aspects including barriers to eliciting a patient narrative, involving patient and family members, and documenting SLT. Conclusions & Implications: This study provides information that can be used to implement person‐centred care in SLT education, clinical practice, and research by providing an inventory of the current knowledge and the existing gaps. What is already known on the subject: PCC has shown positive effects and is currently being implemented in various health‐care settings worldwide. What this paper adds to existing knowledge: This study provides an account of the current state in research and practice on how PCC for adults is described, discussed, and evaluated. While related concepts such as family‐centred care have mainly been explored within paediatrics, little is known about how PCC manifests in SLT for adults. Our results show that PCC is presently being discussed and valued in SLT although obstacles exist, and few studies explore whether current practice is person centred and the potential effects of such practice. What are the potential or actual clinical implications of this work?: This study provides clinicians, researchers, and policymakers' guidance on what aspects to consider when working to implement person‐centred SLT for adults.